Perceived Preparedness to Implement Evidence-Based Practice by Certified Rehabilitation Counselors: A Qualitative Content Analysis. (July 2017) - Fitzgerald, Sandra; Leahy, Michael J.; Kang, Hyun-Ju; Chan, Fong; Bezyak, Jill
The implementation of evidence-based practice (EBP) in rehabilitation counseling has the potential to improve the effectiveness of vocational rehabilitation (VR) services and employment outcomes of people with disabilities. The purpose of this content analysis was to explore certified rehabilitation counselors' (CRCs) perceptions of the effectiveness of EBP and their preparedness to implement EBP in a variety of rehabilitation counseling settings. Three hundred fourteen CRCs responded to two open-ended questions related to their perceived effectiveness and preparedness to use EBP in VR service delivery practices. Results of this content analysis indicate that CRCs generally recognize the value of EBP and support its use in rehabilitation counseling. However, they identified major individual-level and organizational-level barriers that could hinder the implementation of EBP in the professional practice of rehabilitation counseling. Strong administrative support, adequate funding, time, and continuous training to update skills will be needed to fully implement EBP in rehabilitation counseling.